Mechanochemically Gated Photoswitching: Expanding the Scope of Polymer Mechanochromism - Barber, Ross W.; McFadden, Molly E.; Hu, Xiaoran; Robb, Maxwell J. (Synlett, 2019)
Mechanophores are molecules that undergo productive, covalent chemical transformations in response to mechanical force. Over the last decade, a variety of mechanochromic mechanophores have been developed that enable the direct visualization of stress in polymers and polymeric materials through changes in color and chemiluminescence. The recent introduction of mechanochemically gated photoswitching extends the repertoire of polymer mechanochromism by decoupling the mechanical activation from the visible response, enabling the mechanical history of polymers to be recorded and read on-demand using light. Here, we discuss advances in mechanochromic mechanophores and present our design of a cyclopentadiene–maleimide Diels–Alder adduct that undergoes a force-induced retro-[4+2] cycloaddition reaction to reveal a latent diarylethene photoswitch. Following mechanical activation, UV light converts the colorless diarylethene molecule into the colored isomer via a 6π-electrocyclic ring-closing reaction. Mechanically gated photoswitching expands on the fruitful developments in mechanochromic polymers and provides a promising platform for further innovation in materials applications including stress sensing, patterning, and information storage.1 Introduction to Polymer Mechanochemistry2 Mechanochromic Reactions for Stress Sensing3 Regiochemical Effects on Mechanophore Activation4 Mechanochemically Gated Photoswitching5 Conclusions
Keywords: polymer mechanochemistry; mechanophore; diarylethene; photoswitch; mechanochromism; Diels–Alder reaction